2006
DOI: 10.1055/s-2005-858858
|View full text |Cite
|
Sign up to set email alerts
|

Zur Therapie des konsekutiven Strabismus divergens

Abstract: The diagnostic value of preoperative prismatic correction of the deviation is very limited. Even if diplopia can be provoked, the chance of disturbing diplopia is very low. Nevertheless, some guidelines for pre- and postoperative care are necessary to prevent double vision. The postoperative outcome is favourable for the patient after one operation. In cases of relapsing divergence a second operation is easily possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Kolling G. H. and Schmidt-Bacher A. [13] have noticed the development of an exodrift after three months of follow up, the mean value was-6 degrees, the dose-effect relation was reduced to 1.4 degrees/mm from 2 degrees/mm operative amount. Yoonae A Cho et al [12] concluded that the corrective value of Medial rectus advancement is 3 PD per 1 mm; Marcon G.B et al [11] results were a little bit different, the mean dose-effect being 5 PD at first day after surgery and 4 PD at 6 month.…”
Section: Discussionmentioning
confidence: 98%
“…Kolling G. H. and Schmidt-Bacher A. [13] have noticed the development of an exodrift after three months of follow up, the mean value was-6 degrees, the dose-effect relation was reduced to 1.4 degrees/mm from 2 degrees/mm operative amount. Yoonae A Cho et al [12] concluded that the corrective value of Medial rectus advancement is 3 PD per 1 mm; Marcon G.B et al [11] results were a little bit different, the mean dose-effect being 5 PD at first day after surgery and 4 PD at 6 month.…”
Section: Discussionmentioning
confidence: 98%